PELABUHAN BONERATE: PUSAT NIAGA ANTARPULAU DI SELAYAR (2007-2018) - Bahri; La Malihu; Ahmadin; Najamuddin; Bustan; Salahuddin (Universitas Negeri Makassar, 2023)
This study aims to describe the development of the Port of Bonerate both in terms of infrastructure and the development of loading and unloading of goods and passengers. The research method used is historical research with procedures; heuristics, verification, interpretation and historiography. The results of this study indicate that in Bonerate Island initially there was only one port named Bonerate Harbor which was established in 2007. The waters of the Bonerate Harbor are very strategic because of its very safe position from the waves crashing in both the western and eastern seasons. The physical development of Bonerate Port is quite significant, namely experiencing development of 3 stages in the period 2007-2012. In 2007-2018 Bonerate Port facilities and infrastructure underwent construction in the form of port waters, mooring facilities, warehousing facilities and port facilities. The loading and unloading process of goods at this port experiences ups and downs.